Development Cost Capitalization During R&D Races - De Waegenaere, Anja; Sansing, Richard C.; Wielhouwer, Jacco L. (Contemporary Accounting Research, 2017)
Abstract We investigate the economic effects of capitalizing development costs during a race between two firms to discover and develop a new technology. Winning the race requires success in the research stage and success in the development stage. Development costs are expensed in some settings, but capitalized in others. Capitalization of development costs provides a credible signal regarding progress in the race, allowing the rival to make a more informed decision regarding whether to proceed with development. We study the effects of this signal on the firms’ investment decisions and social welfare. We show that if both firms capitalize instead of expense development costs, aggregate investment in research weakly increases but aggregate investment in development weakly decreases. We also characterize the accounting policies that the two rival firms would adopt if they could freely choose either an expensing policy or a capitalization policy.